Characterization of solid content and distinction between type A and B crystals of TBAB hydrates by Time Domain NMR. (22nd December 2015) - Rondeau-Mouro, C.; Delahaye, A.; Cambert, M.; Fournaison, L.; Mariette, F.
Abstract: Semiclatrate hydrate crystals of tetra- n -butyl ammonium bromide (TBAB) form at atmospheric pressure and at positive temperature. In suspension with water, they can be used as a heat transport medium or for gas separation. In terms of thermal energy storage and secondary refrigeration applications, TBAB hydrate slurries may be characterized by their flow properties under specific thermophysical conditions. The study presented here investigated one of these important properties, i.e. the crystal content, also called the solid fraction, that is usually estimated using the TBAB:H2 O phase diagram. Our investigations revealed that Time-Domain Nuclear Magnetic Resonance (TD-NMR) relaxometry was remarkably sensitive to the solid content of TBAB:H2 O hydrate slurries. Non-invasive and non-destructive measurements performed in real time demonstrated the power of NMR relaxometry to identify and quantify TBAB hydrates. Most importantly, NMR both measured and quantified type A and B hydrates, which no other technique can achieve without destroying the crystals or can only perform theoretically on the basis of a phase diagram, and thus without considering the possible conversion of type A to type B hydrates. Graphical abstract: Highlights: TD-NMR is nondestructive and can quantify the crystal content in hydrate slurries. TD-NMR both characterizes and quantifies the TBAB:H2 O hydrate polymorphism. TD-NMR considers the possible conversion of TBAB:H2 O type A to type B hydrates.